SISTEMATIKA PELAFALAN HURUF KANJI UNTUK NAMA ORANG DAN NAMA TEMPAT DI JEPANG DALAM KONTEKS BACAAN BAHASA JEPANG - Novi Andari (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2012)
Abstrak. This article explores the tradition of giving name in the Japanese society. Japanese people use the Kanji to write their names. The fact that each of the letter in the Kanji contains a single meaning affects the meaning of the names of the Japanese people. In addition, for the Japanese people, it is more comfortable for them to write their names in the Kanji.Â Kata kunci: definisi nama, makna di balik nama orang JepangÂ